Incidencia de la ley Orgánica de Economía Popular y Solidaria en las Cooperativas de Ahorro y Crédito del cantón Latacunga del 1 de enero al 31 de diciembre del 2013 - Chávez Caiza, Evelyn Maritza (2015)
The purpose of this study was to determine the impact of the Organic Law and Regulations on credit unions in Latacunga Canton. It also verifies financial entities’ proper compliance with the Law and Regulations outlined in the governmental policy of Sumak Kawsay (“Good Living”) during the fiscal year 2013. Socio critical analysis reveals the causes and effects of the law, including the impact on inhabitants. In addition, it was determined that the conclusions with their respective recommendations will permit the optimal compliance of the Credit Unions with regard to popular and solidarity economy. The analysis of the impact of the Organic Law on popular and solidarity economy is a permanent evaluation tool since it shows a general approach on the political purpose about the implementation of this Law….